Two Cases of Spontaneous Recurrent Hemarthrosis of the Shoulder with Acromial Erosion Associated with Impingement Syndrome - Shoji Fukuta; Katsutoshli Miyatake; Tetsuya Matsuura; Koichi Sairyo (Case Reports in Orthopedics)
Spontaneous recurrent hemarthrosis of the shoulder is rare. Most previously reported cases were associated with massive rotator cuff tear and degenerative glenohumeral arthritis. We described two cases of recurrent hemarthrosis without osteoarthritis of the shoulder. Both cases had bony erosion of the acromion, which was confirmed arthroscopically as the origin of bleeding. Arthroscopic coagulation, acromioplasty, and drainage were successful and there was no recurrence of hemorrhage.